IMPLEMENTASI PROGRAM KETAHANAN PANGAN DALAM BIDANG PERTANIAN DI DESA MAYANG SARI - Seri Hartati; Mhd Rafi Yahya; Sutrisno Sutrisno (LPPM Universitas Abdurrab, 2024)
This research aims to examine the implementation of food resiliencecprograms, including: the implementation of food resilience programs in the field of red chili farming in Mayang Sari Village, the causes of not optimal implementation of food security programs in the village. Based on pre-research research, it is known that Mayang Sari Village was the village that started the food security program first even though it used private funds and land and did not receive support from the village government. This study used qualitative research methods. The types and sources of data in this research consist of primary data and secondary data whose sources were obtained through interviews and documentation, then analyzed qualitatively. Meanwhile, the theory used is Siagian Theory regarding things that must be considered in implementing a program. The results of the research show that there are criteria for implementing a food security program, namely: targets to be achieved, the need for a time period to complete the work, costs required, types of activities to be carried out, and skilled workers in their respective fields. This shows that it has not been implemented effectively. The causes that influence the implementation of food security programs in the agricultural sector are the village government itself and natural factors.